2022
DOI: 10.35762/aer.2021.44.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study and First Evidence of Presence of Microplastics in Green Mussel, Perna viridis from Phuket

Abstract: Plastics can reach the coastal environment and could impact the marine environment. Mussels are marine organisms which are prone to be exposed to microplastics pollution. Therefore, in this preliminary study, the commercially important green mussel (Perna viridis) collected at the Koh Phee Canal in Phuket, Phuket Province, southern peninsular Thailand, was investigated. The collected mussels from aquaculture farm fell into three age groups, namely 1 year-1 month, 1 year-7 months, and 1 year-9 months. Results f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…The average amount of microplastic in green mussels was 0.15 ± 0.41 (45.63 items/Kg wet weight) and 0.22 ± 0.57 particles/individual (70.16 items/Kg wet weight) in the dry and wet seasons, respectively. The level of microplastics in this study was relatively lower than those reported in other studies despite using different methods for analyzing microplastics, such as those for green mussel (Perna viridis) in Ban Don Bay [39]; blue mussel (Mytilus edulis) and Pacific oyster (Crassostrea gigas) from the French Atlantic coast; green mussel in France [72]; and green mussel (Perna viridis) from Phuket [40], as in Table 3. Interestingly, [73] found very high levels of contamination with 34 to 178 items/individual in mussels in Canada, but their work was based on visualization only.…”
Section: Abundance and Characteristics Of Microplastics In Green Musselscontrasting
confidence: 56%
See 1 more Smart Citation
“…The average amount of microplastic in green mussels was 0.15 ± 0.41 (45.63 items/Kg wet weight) and 0.22 ± 0.57 particles/individual (70.16 items/Kg wet weight) in the dry and wet seasons, respectively. The level of microplastics in this study was relatively lower than those reported in other studies despite using different methods for analyzing microplastics, such as those for green mussel (Perna viridis) in Ban Don Bay [39]; blue mussel (Mytilus edulis) and Pacific oyster (Crassostrea gigas) from the French Atlantic coast; green mussel in France [72]; and green mussel (Perna viridis) from Phuket [40], as in Table 3. Interestingly, [73] found very high levels of contamination with 34 to 178 items/individual in mussels in Canada, but their work was based on visualization only.…”
Section: Abundance and Characteristics Of Microplastics In Green Musselscontrasting
confidence: 56%
“…In Thailand, microplastic pollution has been reported in many areas, such as estuarine water at the Chaopraya River mouth [35], beaches [36,37], sediments in the urban estuary in Phuket Province [38], and marine organisms [31,39,40]. Unfortunately, the degree and evaluation of microplastics in coastal farming areas are rarely established and unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The chemotaxis proteins and membrane components were found to be upregulated [121]. Recent reports are showing contamination of different types of waters with microplastic [122]. Mangrove rhizosphere isolates were found to colonize microplastic.…”
Section: ) Other Compoundsmentioning
confidence: 92%
“…Morphometrics is a method of measuring the external shape of the body, which is used as a basis for comparing the size of green mussels (Perna viridis), such as width, standard length, height and others. Morphometric measurements are useful for knowing the growth patterns, feeding habits and groups of Perna viridis and as a basis for fish identification [17]. Morphometric characters that are often used for measurement include total length, standard length, claw length, body height and width, fin height and length, and eye diameter [18].…”
Section: Morphometric Collection Data and Analysis Of Perna Viridismentioning
confidence: 99%